The Biblical World. A Dictionary of Biblical Archaeology (1966)
Consulting Editors E. Leslie Carlson - Claude F. A. Schaeffer - J. A. Thompson; articles by G. Giасumakis, Jr., William Hallo, Harry Hoffner, A. F. Rainey, Edwin Yamauchi et al. on cuneiform subjects.